Annotated checklist of the decapod crustaceans of the Gulf of Oman, northwestern Indian Ocean - Naderloo, Reza; Ebrahimnezhad, Saeed; Sari, Alireza (Zootaxa, 2015)
The decapod crustaceans of the Gulf of Oman have been documented based on the published literature and new sampling along the Iranian coast between 2005 and 2015. A total of 121 species were collected along the Iranian coast, of which 43 are new records for the Gulf of Oman. The Decapoda of the Gulf is currently represented by 258 species belonging to five infraorders: Axiidea, Achelata, Anomura, Brachyura, and Caridea. Brachyura, with 176 species, are the best represented group, followed by Anomura and Caridea with 42 and 17 species, respectively. The least diverse groups are Achelata, with five species, and Axiidea, with three. On the basis of the available information, the northern (Iranian) coast with 189 species is more diverse than the southern (United Arab Emirates and Oman) coast with 134 species.